Effect of Chronic Consumption of Sweeteners on Microbiota and Immunity in the Small Intestine of Young Mice - B. E. Martínez-Carrillo; C. A. Rosales-Gómez; N. Ramírez-Durán; A. A. Reséndiz-Albor; J. A. Escoto-Herrera; T. Mondragón-Velásquez; R. Valdés-Ramos; A. Castillo-Cardiel (International Journal of Food Science, 2019)
The consumption of sweeteners has increased as a measure to reduce the consumption of calories and thus combat obesity and diabetes. Sweeteners are found in a large number of products, so chronic consumption has been little explored. The objective of the study was to evaluate the effect of chronic sweetener consumption on the microbiota and immunity of the small intestine in young mice. We used 72 CD1 mice of 21 days old, divided into 3 groups: (i) No treatment, (ii) Group A (6 weeks of treatment), and (iii) Group B (12 weeks of treatment). Groups A and B were divided into 4 subgroups: Control (CL), Sucrose (Suc), Splenda® (Spl), and Svetia® (Sv). The following were determined: anthropometric parameters, percentage of lymphocytes of Peyer’s patches and lamina propria, IL-6, IL-17, leptin, resistin, C-peptide, and TNF-α. From feces, the microbiota of the small intestine was identified. The BMI was not modified; the mice preferred the consumption of Splenda® and Svetia®. The percentage of CD3+ lymphocytes in Peyer’s patches was increased. In the lamina propria, Svetia® increased the percentage of CD3+ lymphocytes, but Splenda® decreases it. The Splenda® and Svetia® subgroups elevate leptin, C-peptide, IL-6, and IL-17, with reduction of resistin. The predominant genus in all groups was Bacillus. The chronic consumption of sweeteners increases the population of lymphocytes in the mucosa of the small intestine. Maybe, Bacillus have the ability to adapt to sweeteners regardless of the origin or nutritional contribution of the same.